The Role Of Healthcare Professionals In Enhancing And Accelerating Patient Recovery: A Systematic Review (The Review of Diabetic Studies, 2025)
Patient recovery speed is a critical indicator of healthcare quality, resource efficiency, and patient satisfaction. Healthcare professionals—nurses, physicians, physiotherapists, pharmacists, dietitians, and psychosocial support staff—play a vital role in accelerating the healing trajectory through evidence-based interventions and coordinated care. This systematic review synthesizes recent literature (2016–2025) examining how multidisciplinary healthcare teams influence and enhance the patient healing process. The review explores clinical interventions, communication practices, psychosocial support, early mobilization strategies, medication optimization, and the integration of digital tools that collectively contribute to faster recovery. Using PRISMA guidelines, relevant studies were identified across major databases including PubMed, Scopus, CINAHL, and Web of Science. Findings reveal that patient-centered communication, rapid assessment, interprofessional collaboration, early rehabilitation, adherence to enhanced recovery protocols, and personalized care plans significantly reduce complications and length of hospital stay. Additionally, the presence of skilled nursing care, structured physiotherapy sessions, and pharmacist-led medication reviews emerged as essential accelerators of patient healing. The review concludes that a coordinated, holistic, and evidence-based approach by healthcare professionals can substantially improve patient recovery speed and outcomes. Recommendations emphasize enhanced training, digital integration, and multidisciplinary teamwork to support accelerated healing in diverse healthcare settings.